Effects of Silybum marianum Aqueous Extract and L-carnitine on Stereological Changes in Diazinon-Treated Rat Liver - Forough Masoumi; Mehrdad Shariati; Mokhtar Mokhtari (Indonesian Center for Animal Research and Development (ICARD), 2020)
As an organophosphorus, Diazinon (DZN) impairs liver tissue function by inhibiting acetylcholinesterase and causing oxidative stress. In this study, the effects of Silybum marianum aqueous extract (SMAE) and L-carnitine (LC) on the stereological and histopathological changes of the liver in DZN-treated male rats were investigated. The rats in this study were placed into 9 groups of 8 each containing control, placebo, and a combination of DZN, SMAE, and LC. The animals received SMAE and chemicals orally for 30 days. At last, the liver tissue of all animals was removed. Then, tissue sections from the liver were provided to study the stereological markers including liver volume and weight, hepatocytes’ volume, central venous volume, sinusoidal volume, connective tissue volume, inflammation rate, and a number of the hepatocytes’ nuclei. Also, the sample tissues were evaluated histopathologically. Treatment with DZN significantly reduced the liver volume and weight, hepatocyte volume, central venous volume, sinusoidal volume, and hepatocyte nucleus number compared to placebo and control but it significantly increased the inflammation and volume of liver’s connective tissue. However, co-administration of SMAE and LC with DZN improved liver volume and weight, hepatocyte volume, central venous volume, sinusoidal volume, connective tissue volume, and hepatocyte nucleus number alone compared to the DZN treatment. Liver inflammation was also significantly decreased compared to the DZN treatment but comparing to the placebo and control groups, it increased significantly. Simultaneous administration of SMAE and LC has protective effects on liver tissue and can reduce DZN-induced liver injury in rats.